1997
DOI: 10.1002/(sici)1097-4601(1997)29:1<17::aid-kin3>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Activation parameters of ferryl ion reactions in aqueous acid solutions

Abstract: Stock solution of ozone was prepared by bubbling the effluent from an Erwin Sander (V) ozonator through an aqueous HClO 4 solution. Ozone concentrations of (2.5Ϫ3.0) ϫ 10 Ϫ4 M were achieved without any special procedure. The ozone concentration was determined spectrophotometrically at its maximum absorption wavelength, max ϭ 260 nm, using an ApparatusFor the kinetic studies a Hi-Tech SF 51 Stopped-flow spectrophotometer (SFS) with UV and VIS lamps was used. This instrument has a mixing time of about 1 -2 ms, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…However, Logager et al (1992) provided final evidence that this reaction between Fe(II) and ozone produces Fe(IV) (the ferryl ion) and oxygen (R16). Rate constants and activation energies for reactions of the ferryl ion with selected inorganic and organic compounds present in atmospheric water have been measured by Jacobsen et al (1997a;1998b) (reactions R2, R12, R15, R27, R18, R24, R27, R28, R36, R37, R38, R39). In all Fe(IV) reactions, Fe(III) is formed.…”
Section: Transition Metal Ions Chemistrymentioning
confidence: 90%
See 1 more Smart Citation
“…However, Logager et al (1992) provided final evidence that this reaction between Fe(II) and ozone produces Fe(IV) (the ferryl ion) and oxygen (R16). Rate constants and activation energies for reactions of the ferryl ion with selected inorganic and organic compounds present in atmospheric water have been measured by Jacobsen et al (1997a;1998b) (reactions R2, R12, R15, R27, R18, R24, R27, R28, R36, R37, R38, R39). In all Fe(IV) reactions, Fe(III) is formed.…”
Section: Transition Metal Ions Chemistrymentioning
confidence: 90%
“…The formation of dimer Fe(OH) 2 Fe 4+ is favoured at higher temperature (R19). Afterwards, this species produces also Fe 3+ (R20 and R21) but with a very slow rate (Jacobsen et al, 1997a). For a pH around 3, the ferryl ion plays a role mainly as a temporary OH radical sink whereas for more acidic solution, the ferryl ion is more likely to react as a distinct species (Jacobsen et al, 1998b).…”
Section: Transition Metal Ions Chemistrymentioning
confidence: 99%
“…S3 shows the absorption spectra of Fe 3+ , Fe 2+ , Oxone and Fe 3+ /Oxone solutions. It is known that FeO 2+ exhibits strong absorption at the wavelength of 320 nm [45]. As indicated in Fig.…”
Section: Ibp Degradation Under Different Conditionsmentioning
confidence: 92%
“…S2 also shows the redox potentials of reaction (3) solution are lower than that of the solution containing IBP and Oxone, which is due to the consumption of Oxone and the transformation of Fe 3+ to Fe 2+ . In previous studies, the formation of ferryl-ion (FeO 2+ ) was reported both in traditional Fenton reaction [43,44] and Fe 2+ /O 3 system [45,46]. Fig.…”
Section: Ibp Degradation Under Different Conditionsmentioning
confidence: 99%
“…Since the original constant k 35 = 1.3 Â 10 À2 M À1 s À1 corresponds to kinetics of order 2 (FeO 2+ + H 2 O), the equivalent constant for order 1 is obtained by multiplying k 35 by [H 2 O]. In addition, the FeIVðOHÞ 2þ 2 complex symproportionates with the Fe 2+ ion according to two reaction pathways (Reactions (36a) and (36b)) [15,36,37]. It reacts also with H 2 O 2 (Reaction (37)) and with HO 2 and OH radicals (Reactions (38) and (39) …”
Section: Reactions Of Fe(ii) With H 2 Omentioning
confidence: 99%